(untitled) (Journal Of Educational and Psychological Researches, 2017)
The current study has sought to identify the levels of the compound thinking among secondary school students basing and relying on the opinions of Lipman who sees that the compound thinking consists of creative thinking and critical thinking, In accordance with this point of view, researchers have resorted to build scale of the critical thinking in its final form of (28) item additionally to the adoption of Torrance for the creative thinking which was translated by sayed. Khairallah in 1981 after confirming psychometric Properties Of both scales and then collect scores of both scales and be the final score represented the level of the compound thinking that has been shown by the results of secondary school students they have no skill of the compound thinking . It has shown , on other hand , that there were no significant differences in favor of males in the skill level of the compound thinking as well as it has shown scientific specialization advantage over specialization humanitarian in the level of possession of the skill of the compound thinking and there was no interaction between gender "sex" and specialization in the level of the compound thinking as well as the research has focused and found a set of recommendations and proposals , the most important one is concentrated in the need to develop the quality of teaching and methods in order to be able to develop the type of thinking methods, it has also recommended in the current research the critical need to conduct similar studies to determine the level of critical thinking among secondary school teachers